DNA polymerases in polyoma virus-infected mouse kidney cells. - Wintersberger, U (1975)
Infection of arrested mouse kidney cells by polyoma virus results in the induction of the cellular 6-8S DNA polymerase activity. Levels of this enzyme increase two- to threefold in the cytoplasm but seven- to tenfold in nuclei and nuclear extract, suggesting an accumulation of the enzyme in the nucleus. Experiments using the inhibitor of DNA synthesis, fluordeoxyuridine, indicate that this accumulation is linked to active DNA synthesis. The activity and cellular distribution of the small 3.4S DNA polymerase remains unchanged.